ANALISIS GAYA BAHASA PADA NOVEL JALAN PASTI BERUJUNG KARYA BENYARIS ADONIA PARDOSI DAN PEMANFAATANNYA SEBAGAI RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DI SMA - Astutik, Novia; Danugri, Dadang; Hartanti, Dian (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This study aims to describe the results of the analysis of language style in the novel Jalan Pasti Berujung by Benyaris Adonia Pardosi. The final result of this research is its use as lesson plan. This type of research is descriptive research with descriptive analysis method. Descriptive method of analysis is done by describing the facts which are then followed by analysis. The data of this research is in the from of text along with quotations related to language style. The data collection technique ysed is a literature study technique. From the results of the research, it can be concluded that the novel Jalan Pasti Berujung by Benyaris Adonia Pardosi contains figurative language which includes: a) Comparative language styles are metaphor, personification, allegory; b) Contradictions include hyperbole, paradox, irony, and sarcasm; c) There is a link between synecdoche, metonymy, and allusions; d) Repettition has chiasmus, anaphora, aand mesodilopsisi language style.